The vasopressin V1b receptor critically regulates hypothalamic-pituitary-adrenal axis activity under both stress and resting conditions - Tanoue, Akito (American Society for Clinical Investigation, 2004)
The neurohypophyseal peptide [Arg(8)]-vasopressin (AVP) exerts major physiological actions through three distinct receptor isoforms designated V1a, V1b, and V2. Among these three subtypes, the vasopressin V1b receptor is specifically expressed in pituitary corticotrophs and mediates the stimulatory effect of vasopressin on ACTH release. To investigate the functional roles of V1b receptor subtypes in vivo, gene targeting was used to create a mouse model lacking the V1b receptor gene (V1bR–/–). Under resting conditions, circulating concentrations of ACTH and corticosterone were lower in V1bR–/– mice compared with WT mice (V1bR+/+). The normal increase in circulating ACTH levels in response to exogenous administration of AVP was impaired in V1bR–/– mice, while corticotropin-releasing hormone–stimulated ACTH release in the V1bR–/– mice was not significantly different from that in the V1bR+/+ mice. AVP-induced ACTH release from primary cultured pituitary cells in V1bR–/– mice was also blunted. Furthermore, the increase in ACTH after a forced swim stress was significantly suppressed in V1bR–/– mice. Our results clearly demonstrate that the V1b receptor plays a crucial role in regulating hypothalamic-pituitary-adrenal axis activity. It does this by maintaining ACTH and corticosterone levels, not only under stress but also under basal conditions.